2013
DOI: 10.1016/j.acthis.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A comparative histochemical study of the distribution of mucins in the gastrointestinal tracts of three insectivorous mammals

Abstract: a b s t r a c tThe distribution of mucous secreting goblet cells was examined in the gastrointestinal tracts of three insectivores namely: Acomys spinosissimus (Southern African spiny mouse), Crocidura cyanea (Reddish gray musk shrew) and Amblysomus hottentotus (Hottentot golden mole) in order to improve our understanding of the quality and composition of the protective intestinal biofilm. Intestinal tracts were fixed and processed to wax for histology. Serial transverse sections were stained using alcian blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(45 citation statements)
references
References 26 publications
(47 reference statements)
12
33
0
Order By: Relevance
“…This was true in M. rex in the present study where the number of sulfomucin secreting goblet cells increased significantly towards the distal GIT. In accordance, Boonzaier et al (2013) observed significantly higher numbers of sulfomucin secreting cells in the large intestine than the duodenum in C. cyanea and A. spinosissimus.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…This was true in M. rex in the present study where the number of sulfomucin secreting goblet cells increased significantly towards the distal GIT. In accordance, Boonzaier et al (2013) observed significantly higher numbers of sulfomucin secreting cells in the large intestine than the duodenum in C. cyanea and A. spinosissimus.…”
Section: Discussionsupporting
confidence: 71%
“…The small intestine of A. spinosissimus, Crocidura cyanea (Boonzaier et al, 2013) and humans (Subbuswamy, 1971) contains predominantly neutral mucin secreting goblet cells, but this was not the case in the species in the current study, as mixed mucin secreting cells was the predominant type in the small intestine. A trend of exclusively acid mucins secreting cells increasing steadily from the duodenum to the distal colon was noted in A. spinosissimus ( Boonzaier, 2012) and M. rex (present study).…”
Section: Discussionmentioning
confidence: 39%
See 3 more Smart Citations